Liquid CO phase transition fracturing technology and its application in enhancing gas drainage of coal mines - Yingchun Fan; Botao Qin; Qun Zhou; Quanlin Shi; Dong Ma; Jiahao Wu (Adsorption Science & Technology)
Liquid CO 2 phase transition fracturing (LCO 2 -PTF) is an effective and economical technology used to improve the permeability of rock and coal. In this study, the working mechanisms of LCO 2 -PTF were analysed and relevant equipment was designed to develop and promote the application of this technology. It utilized phase transition equipment (PTE) consisting of a liquid gas container, control unit for the current and gas volume, heating tube, and other components. LCO 2 blasting experiments were conducted in an airtight container to investigate the released energy, pressure, and other technical parameters. The application of LCO 2 -PTF for enhancing gas drainage in coal mines was then evaluated. The results of a blasting experiment showed a maximum energy of 947.12 kJ and revealed that the releasing pressure could be easily changed by varying the plate and heat tube. The releasing pressure remained unchanged within an initial distance and then decreased exponentially. The blasting products were gaseous CO 2 and water vapor, with no sparks or flames. The surface temperature of the PTE ranged from 269.32 to 277.96 K. Application of LCO 2 -PTF in coal mines with low permeability showed gas drainage 3.38 times higher than that achieved with conventional technologies, with methane concentration increasing from 55 to 89%. The attenuation coefficient of gas emissions dropped by 94% and the gas permeability coefficient of the coal body increased more than 23 times after fracturing. The shockwave of the high-pressure gas promoted the development and extension of cracks. The influence radius of the pre-cracking coal seam was 8.1 m, which is 6.75 times that of the original coal seam. The experimental results and the engineering applications indicate that LCO 2 -PTF is a safe and effective technology to enhance gas drainage in coal mines.